Crab Mentality Dalam Al-Qur’an (Interpretasi Q.S Al-Nisa [4]: 54-55 Pada Tafsir MafaTih Al-Ghayb Karya Fakhruddin Al-Razi) (As-Sahla: Journal Of Islamic Studies, 2025)
Crab Mentality is an analogy of being selfish and jealous of other people's success. This phenomenon can be found in various aspects of life such as in offices, organizations, and even families. In the Qur'an, there are several verses that explain the phenomenon of crab mentality with different derivation of terms. One of the terms used to indicate the nature of crab mentality is the memorization of hasad in Q.S Al-Nisa: 54-55. Research on crab mentality is an interesting thing to study because it can help people understand how the Qur'an discusses crab mentality, and how this trait can affect people's lives and how to overcome this trait. This research will analyze the phenomenon of crab mentality in Q.S Al-Nisa: 54-55 in tafsir mafatih Al-Ghayb. This research uses library research method with content analysis approach. The results showed that crab mentality originated from envy and hatred of someone's enjoyment. This is in accordance with the definition of hasad, which wants the pleasure to disappear.